An Increase in Cellular Size Variance Contributes to the Increase in Ultrasound Backscatter During Cell Death - Vlad, Roxana M.; Saha, Ratan K.; Alajez, Nehad M.; Ranieri, Shawn; Czarnota, Gregory J.; Kolios, Michael C. (Ultrasound in medicine & biology, 2010)
This study aims to explain the contribution of changes in cellular size variance (CSV) to increases in ultrasound-integrated backscatter (UIB) measured from cell samples undergoing cell death. A Monte Carlo algorithm was used to compare simulations of 2D distributions of cells, uniform (CSV = 0) versus heterogeneous (CSV > 0) and the same mean cellular size ( M ¯ ). UIB increased in arrangements with heterogeneous cellular sizes from 3.6dB ( M ¯ = 20 μm, CSV = 0 μm/CSV = 18 μm) to 5.6 dB ( M ¯ =10 μm, CSV = 0 μm/CSV = 8 μm). Experimentally, UIB (10 to 30 MHz) was measured from cell samples of four tumor cell lines viable and undergoing cell death after radiotherapy and chemotherapy treatment. An increase of 3.8–7.5 dB ( p < 0.001) in UIB was measured from three cell lines. No increase in UIB was measured from one cell line. An increase in CSV was found for all cell samples after cell death. The results suggest that an increase in CSV could have a significant contribution to the increases measured in UIB after cell death in cell samples exposed to anticancer therapies. (E-mail: rvlad@lakeridgehealth.on.ca)